Sistem IJON Sebagai Bentuk Kearifan Lokal Dalam Sistem Perikatan Di Desa Colol, Kec. Lambaleda Kab. Manggarai Timur - Laura Berenika Apriliani Tija; Genoveva Sumanti; Renita Sepriani R. Lepuan; Delfiana Bani; Laurensius Kaba Dami; Elias Bertolomeus Neu Roga; Stefanus Don Rade (Universitas Sains dan Teknologi Komputer, 2024)
One of the local wisdom in Manggarai that relates to agreement or engagement is the ijon system. Basically, the ijon system is asystem of agreement or trade ia an item that arises in the community that is not clear about the goods or thre results that will be obtained. The method that is appropriate or has relationship with the material that we will discuss, namely the descriptive research method. Descriptive research method is research that aims to describe something is acertain area and at a certain time. Usually in this reseach the research already gets or already has a picture in the form of initial data about the problem to be studied. Buying and selling coffee with a bond system is not made in writing but is only confirmed by the buyer’s deposit receipt. In the practice of the coffee bond system in Colol village, two parties are involved, namely: 1. Coffee Farmers 2. Ijon Buyers/Middlemen to solve any problems related to the bond system in their Village, can use several alternatives and step taken by Colol villagers if a problem occur, namely: 1. Done in a family way 2. Done at the village office 3. Done in court.